ORIENTARE SPRE CULTURA SERVICIILOR - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The „B.P. Hasdeu” Municipal Library’s librarians are finding the way to excellent services, focusing on the service culture education. At the public cafe based on the topic „Orientation to service culture” the librarians discussed many topics approaches, typology, problems and implementation of services. In order to fortify the results of discussions the participants have completed a „Services tree” and a survey „Do you provide a good services to your users?”. The survey has 10 questions (Anexe 1. Survey. Questions), taken from CILIP guidelines. The results express the status quo in the approach of services at the branches and at the network level, identify the difficulties and accepted practices, provide ideas that can serve as a basis for improving the status quo and make changes.